2016
DOI: 10.1080/01658107.2016.1243131
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Nerve Fibre Layer Thickness of Migraine Patients with or without White Matter Lesions

Abstract: The aim of this study was to determine whether retinal nerve fibre layer (RNFL) thickness is correlated with cerebral white matter lesions (WML) in migraine patients. Forty migraine and 40 healthy subjects were included in this study. The difference in RNFL thickness between the control and a migraine group with WML and a migraine group without WML were investigated using analysis of variance (ANOVA). A Tukey post hoc test was conducted to determine from which group the difference originated. Lower RNFL thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
2
15
1
Order By: Relevance
“…However, results have not been very consistent. Thus, whereas some authors observed that mean peripapillary RNFL thickness was thinner in migraine patients than in healthy controls, others reported only a thinner RNFL in a specific quadrant ( 16 , 18 , 32 , 56 62 ). This selective RNFL involvement might be associated with differences in the vulnerability of retinal axons to ischemia and with focal perimetric changes ( 63 ).…”
Section: Optic Nerve Structural Changes In Migrainementioning
confidence: 94%
See 4 more Smart Citations
“…However, results have not been very consistent. Thus, whereas some authors observed that mean peripapillary RNFL thickness was thinner in migraine patients than in healthy controls, others reported only a thinner RNFL in a specific quadrant ( 16 , 18 , 32 , 56 62 ). This selective RNFL involvement might be associated with differences in the vulnerability of retinal axons to ischemia and with focal perimetric changes ( 63 ).…”
Section: Optic Nerve Structural Changes In Migrainementioning
confidence: 94%
“…Several authors have used OCT to study possible changes in macular thickness in patients with migraine. Their results are contradictory because, although most found no change in either foveal or macular parameters in migraine patients ( 18 , 59 , 62 ), some reported that foveal thickness (FT) values ( 19 ) or GCL ( 61 , 64 ) were thinner in MwA than in MwoA. The more diminished blood flow in MwA would explain this finding, given that in MwoA, at least between attacks, pulsatile choroidal blood flow is not compromised.…”
Section: Macular Changes In Migrainementioning
confidence: 95%
See 3 more Smart Citations